Plant cell wall integrity maintenance as an essential component of biotic stress response mechanisms - Hamann, Thorsten (Frontiers in Plant Science, 2012)
Plant cell walls provide structural support during development and represent the first line of defense against biotic and abiotic stress. In recent years evidence has accumulated that a dedicated plant cell wall integrity maintenance mechanism exists. This mechanism monitors and maintains functional integrity of the cell wall during different biological processes. The available data suggest that it may represent a component of the stress response mechanisms underlying biotic and abiotic stress responses, which has not been identified previously. Here I will review the available evidence regarding the mode of action of the cell wall integrity maintenance mechanism and discuss its role in the context of biotic plant stress response mechanisms.